Activity of hair tonic preparation combining Apium graveolens L extract, Tussilago farfara flower extract, Achillea millefolium extract, Cinchona succirubra bark extract on male New Zealand white rabbits - Ardi, Maria Yedida; Faizatun, Faizatun; Desmiaty, Yesi (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Numerous hair care products are currently available in the market, including shampoo, conditioner, hair mask, hair serum, and hair tonic. Unlike shampoo, hair tonic remains in contact with the scalp for a longer duration, potentially enhancing its effectiveness. Apium graveolens L (EDS) and a combination of Tussilago Farfara flowers, Achillea Millefolium L leaves, and Cinchona Succirubra L stems, marketed as ATG, are known for their hair growth-promoting properties. This study aimed to evaluate the hair growth efficacy, stability, and safety of a hair tonic formulated from EDS and ATG extracts. The prepared extract solution was applied to the shaved backs of male New Zealand rabbits, aged 4 months and weighing 2.5-3 kg, and observations were recorded on days 7, 14, 21, and 28. Parameters measured included hair length and weight. The results indicated that the F1 formulation yielded an average hair length of 9.89 mm and weight of 49.38 mg; F2, 10.36 mm and 49.5 mg; F3, 11.98 mm and 49.5 mg; F4, 17.44 mm and 60.63 mg; F5, 17.27 mm and 52.75 mg; and F6, 19.06 mm and 56.5 mg. Conclusively, the F6 formulation demonstrated the most significant results, with an average hair length of 19.06 mm and weight of 56.5 mg. The hair tonic formulation was found to be non-irritating to the skin and remained stable throughout the study.